PERSEPSI MASYARAKAT TENTANG KIPRAH KIAI DALAM KANCAH POLITIK - Heri Fadli Wahyudi (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
The legitimacy authority of kiai’s diversity it’s nothing for the Indonesian muslim communities. even for some people, the figure of kiai gets the title as a holy person, wise along with other attributes that are embedded to the kiai. Whereas lately, the picture of politics continues to be torn apart and degenerates so that you are in an uncomfortable zone, thas is a negative view of dirty world. So is there a synergistic meeting point betwen these two poles ? so that both of them can be in tune to become a single. This study aims to determine the publics of kiai, by using the type field qualitative reasearch when  the reasearcher conducts reseacrh in the Somber Bentong hamlet, Karang Cempaka Village, Bluto District, Sumenep regency. to get understanding description, public percepstion and dakwah from political kiai. The techniques used in this research are observation, interview and documentation which are then analyzed by data reduction, data presentation and data verification. The conclusion of this study is that the term kiai undergoes a transformation of function that is only intended for a person with religious understanding who is considered capable. While public perception of kiai figures involved in politics practically does not result in a shift in community compliance. As well as the public's view of da'wah kiai politics remains in the optimistic space of healthy and clean politics.